2021
DOI: 10.3390/pathogens11010016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nigerian Lumpy Skin Disease Virus Isolate after Experimental Infection of Cattle

Abstract: Lumpy skin disease virus (LSDV), together with sheeppox virus and goatpox virus, belong to the genus Capripoxvirus within the family Poxviridae. Collectively, they are considered the most serious poxvirus diseases of agricultural livestock. Due to their severe clinical course and consequent loss of production, as well as high mortality of naïve small and large ruminant populations, they are known to have a significant impact on the economy and global trade restrictions of affected countries. Therefore, all cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…This was most obvious at later timepoints (from 15 dpi). A similar pattern of responses has been observed in previous studies (22, 60, 61), and is likely due to the higher virus load in the clinical calves providing more antigenic-stimulation.…”
Section: Discussionsupporting
confidence: 87%
“…This was most obvious at later timepoints (from 15 dpi). A similar pattern of responses has been observed in previous studies (22, 60, 61), and is likely due to the higher virus load in the clinical calves providing more antigenic-stimulation.…”
Section: Discussionsupporting
confidence: 87%
“…Half of the animals were infected and shared the same airspace with non-infected animals and since representatives of both groups of animals developed LSD, it clearly indicates an alternative indirect contact mode of transmission. In-contact transmission between infected and uninfected animals was suggested when a classical LSDV field strain (LSDV-V/281-Nigeria) was used as an inoculum ( 31 ). The authors reported PCR positive results from nasal swabs from the in-contact animals, but these animals did not produce any clinical signs of viral infection, nor had viraemia detected from blood, nor seroconverted, nor were virus isolation attempted ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In-contact transmission between infected and uninfected animals was suggested when a classical LSDV field strain (LSDV-V/281-Nigeria) was used as an inoculum ( 31 ). The authors reported PCR positive results from nasal swabs from the in-contact animals, but these animals did not produce any clinical signs of viral infection, nor had viraemia detected from blood, nor seroconverted, nor were virus isolation attempted ( 31 ). Since there is no scientific justification to suggest that poxviruses display local replication without disseminating via the lymph and blood ( 32 ), additional studies are required to clarify this issue concerning classical LSDV strains that have thus far been principally associated with transmission via insects.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, LSD is a newly emerging infectious disease with an incidence not previously described in cattle until March 2021 [ 15 ]. LSDV DNA has been extracted from nodules, lymph nodes, ulceration, milk, secretions, semen, and blood of infected cattle [ 8 16 17 29 ]. In the present study, the LSDV was detected in the blood of infected cattle by PCR targeting P32 antigen gene.…”
Section: Discussionmentioning
confidence: 99%
“…LSDV is a double-strand DNA virus. The genome of this virus is easy to detect in a variety of specimens, including nodules, ulceration, secretions, semen, and blood of infected cattle [ 8 16 17 ]. Polymerase chain reaction (PCR) and modified PCR methods targeting p32 and GPCR genes are used widely to detect and characterize LSDV [ 18 19 ].…”
Section: Introductionmentioning
confidence: 99%